A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Farm revegetation has substantial potential to improve biodiversity outcomes - Karel Mokany; Hugh M. Burley; Chris Ware; Katherine M. Giljohann; Anthony P. O'Grady; Karen M. Christie-Whitehead; Matthew T. Harrison (Journal of Environmental Management, 2025)

Phenotypic adaptation to temperature in the mosquito vector, Aedes aegypti - Nina L. Dennington; Marissa K. Grossman; Fhallon Ware‐Gilmore; Janet L. Teeple; Leah R. Johnson; Marta S. Shocket; Elizabeth A. McGraw; Matthew B. Thomas (Global Change Biology, 2024)
Most models exploring the effects of climate change on mosquito‐borne disease ignore thermal adaptation. However, if local adaptation leads to changes in mosquito thermal responses, “one size fits all” models could fail to capture current variation between populations and future adaptive responses to changes in temperature. Here, we assess phenotypic adaptation to temperature in Aedes aegypti , the primary vector of dengue, Zika, and chikungunya viruses. First, to explore whether there is any difference in existing thermal response of mosquitoes between populations, we used a thermal knockdown assay to examine five populations of Ae. aegypti collected from climatically diverse locations in Mexico, together with a long‐standing laboratory strain. We identified significant phenotypic variation in thermal tolerance between populations. Next, to explore whether such variation can be generated by differences in temperature, we conducted an experimental passage study by establishing six replicate lines from a single field‐derived population of Ae. aegypti from Mexico, maintaining half at 27°C and the other half at 31°C. After 10 generations, we found a significant difference in mosquito performance, with the lines maintained under elevated temperatures showing greater thermal tolerance. Moreover, these differences in thermal tolerance translated to shifts in the thermal performance curves for multiple life‐history traits, leading to differences in overall fitness. Together, these novel findings provide compelling evidence that Ae. aegypti populations can and do differ in thermal response, suggesting that simplified thermal performance models might be insufficient for predicting the effects of climate on vector‐borne disease transmission.

The effects of microplastic on the thermal profile of sand: implications for marine turtle nesting grounds - Mariana M. P. B. Fuentes; Valencia Beckwidth; Matthew Ware (Frontiers in Marine Science, 2023)
Introduction Microplastics (i.e., plastic debris smaller than 5mm) found in coastal areas can impact the marine habitat used by endangered species since they may alter sand properties including temperature and permeability. Such alterations may pose a significant threat to marine turtle populations as nest productivity, sexual development, and hatchling fitness are dependent on conditions within the nest, which incubate in the sand. Given that there is a record of microplastic presence at marine turtle nesting sites, this study was conducted to explore the potential influence of microplastics on the thermal profile of sediment typical of marine turtle nesting habitat. Methods The experiment was conducted at the Florida State University Coastal and Marine Laboratory where the temperatures of containers of sand mixed with 5-30% v/v of either black or white microplastics were recorded from July to September 2018. Results The addition of microplastics in the sand resulted in an increase in temperature – 0.017°C for each 1% v/v increase in microplastic. However, the color of the microplastic did not have a significant effect on sand temperature. Overall, the container with 30% v/v black particles had the highest mean temperature increase of 0.58°C (± 0.34°C) over the control. Discussion The results obtained from this study indicate that extreme concentrations of microplastics could be an issue for marine turtles as any changes in sand temperature may affect the sex ratio of hatchlings and/or alter nest productivity.

Zinc on the edge—isotopic and geophysical evidence that cratonic edges control world-class shale-hosted zinc-lead deposits - David L. Huston; David C. Champion; Karol Czarnota; Jingming Duan; Matthew Hutchens; Suzanne Paradis; Mark Hoggard; Bryant Ware; George M. Gibson; Michael P. Doublier; Karen Kelley; Anne McCafferty; et al. (Mineralium Deposita, 2023)
The North Australian Zinc Belt is the largest zinc-lead province in the world, containing three of the ten largest known individual deposits (HYC, Hilton-George Fisher, and Mount Isa). The Northern Cordillera in North America is the second largest zinc-lead province, containing a further two of the world’s top ten deposits (Red Dog and Howards Pass). Despite this world-class endowment, exploration in both mineral provinces during the past 2 decades has not been particularly successful, yielding only two significant discoveries (Teena, Australia, and Boundary, Canada). One of the most important aspects of exploration is to choose mineral provinces and districts within geological belts that have the greatest potential for discovery. Here, we present results from these two zinc belts that highlight previously unused datasets for area selection and targeting. Lead isotope mapping using analyses of mineralized material has identified gradients in μ ( 238 U/ 204 Pb) that coincide closely with many major deposits. Locations of these deposits also coincide with a gradient in the depth of the lithosphere-asthenosphere boundary determined from calibrated surface wave tomography models converted to temperature. Furthermore, gradients in upward-continued gravity anomalies and a step in Moho depth correspond to a pre-existing major crustal boundary in both zinc belts. A spatial association of deposits with a linear mid- to lower-crustal resistivity anomaly from magnetotelluric data is also observed in the North Australian Zinc Belt. The change from thicker to thinner lithosphere is interpreted to localize prospective basins for zinc-lead mineralization and to control the gradient in lead isotope and geophysical data. These data, when combined with data indicative of paleoenvironment and changes in plate motion at the time of mineralization, provide new exploration criteria that can be used to identify prospective mineralized basins and define the most favorable parts of these basins.

A working guide to harnessing generalized dissimilarity modelling for biodiversity analysis and conservation assessment - Karel Mokany; Chris Ware; Skipton N. C. Woolley; Simon Ferrier; Matthew C. Fitzpatrick (Global Ecology and Biogeography, 2022)
Aim Generalized dissimilarity modelling (GDM) is a powerful and unique method for characterizing and predicting beta diversity, the change in biodiversity over space, time and environmental gradients. The number of studies applying GDM is expanding, with increasing recognition of its value in improving our understanding of the drivers of biodiversity patterns and in implementing a wide variety of spatial assessments relevant to biodiversity conservation. However, apart from the original presentation of the GDM technique, there has been little guidance available to users on applying GDM to different situations or on the key modelling decisions required. Innovation We present an accessible working guide to GDM. We describe the context for the development of GDM, present a simple statistical explanation of how model fitting works, and step through key considerations involved in data preparation, model fitting, refinement and assessment. We then describe how several novel spatial biodiversity analyses can be implemented using GDM, with code to support broader implementation. We conclude by providing an overview of the range of GDM‐based analyses that have been undertaken to date and identify priority areas for future research and development. Main conclusions Our vision is that this working guide will facilitate greater and more rigorous use of GDM as a powerful tool for undertaking biodiversity analyses and assessments.

Insights Into Sea Turtle Population Composition Obtained With Stereo-Video Cameras in situ Across Nearshore Habitats in the Northeastern Gulf of Mexico - Tabitha Siegfried; Christopher Noren; Jackson Reimer; Matthew Ware; Mariana M. P. B. Fuentes; Susan E. Piacenza (Frontiers in Marine Science, 2021)
Population size estimates are key parameters used in assessments to evaluate and determine a species’ conservation status. Typically, sea turtle population estimates are made from nesting beach surveys which capture only hatchling and adult female life stages and can display trends opposite of the full population. As such, in-water studies are critical to improve our understanding of sea turtle population dynamics as they can target a broader range of life stages – though they are more logistically and financially challenging to execute compared to beach-based surveys. Stereo-video camera systems (SVCS) hold promise for improving in-water assessments by removing the need to physically capture individuals and instead extract 3D measurements from video footage, thereby simplifying monitoring logistics and improving safety for the animals and surveyors. To demonstrate this potential, snorkel surveys were conducted at artificial habitats in the northeastern Gulf of Mexico (neGOM) to collect size and photo-identification data on sea turtles in situ using a SVCS. Over 29.86 survey hours, 35 sea turtles were observed across three species ( Caretta caretta, Chelonia mydas , and Lepidochelys kempii ) and all neritic life stages (juvenile, sub-adult, and adult) utilizing different habitats, including artificial reefs, jetties, and fishing piers. Greens straight carapace length ranged from 28.55 to 66.96 cm ( n = 23, mean 43.07 cm ± 11.26 cm standard deviation; SD) and loggerheads ranged from 59.71 to 91.77 cm ( n = 10, mean 74.50 cm ± 11.35 cm SD), and Kemp’s ridleys ranged from 42.23 cm to 44.98 cm (mean 43.61 cm ± 1.94 cm SD). Using a linear mixed model, we found that species and habitat type were the most important predictors of sea turtle body length distribution. Overall, this case study demonstrates the potential of SVCS surveys to enhance our understanding of the population structure of sea turtle species within the neGOM and elsewhere.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

Hemodynamic responses to visual stimulation in children with sickle cell anemia - Ping Zou; Kathleen J. Helton; Matthew Smeltzer; Chin-Shang Li; Heather M. Conklin; Amar Gajjar; Winfred C. Wang; Russell E. Ware; Robert J. Ogg (Brain Imaging and Behavior, 2011)